Peers and parental attachment and emotional intelligence among delinquents in rehabilitation centers in Malaysia - Wahab, Rozita; Mansor, Mariani (Human Resource Management Academic Research Society, 2017)
This study examined the effects of parents and peers attachment on emotional intelligence among Malaysian delinquents in government rehabilitation institutions. There were 203 delinquents aged between 11 to 19 years old were randomly selected from six different rehabilitation centres in Wilayah Persekutuan Kuala Lumpur (WPKL), Selangor and Malacca. Respondent’s emotional intelligence was measured using the Assessing Emotional Scale instrument (AES; Schutte, Malouff, Hall, Haggerty, Cooper, Golden, & Dornheim, 1998), while attachment was assessed using the revised version of Instrument of Parent and Peer Attachment (IPPA; Armsden & Greenberg, 1989). Results revealed that mother, father and peer attachment were significantly correlated to emotional intelligence of delinquents in the rehabilitation centres. T-test analysis also indicated that there were no significant differences for mother attachment, peer attachment and emotional intelligence across gender. However, only father attachment was found to be significantly different between male and female delinquents.